A BSP closer to the people spreading the benefits of monetary and financial stability - Diokno, Benjamin E. (2019)
This article tackles the efforts of the Bangko Sentral ng Pilipinas (BSP) to bring the achievement of its core mandates closer to the Filipino people. It examines the complex operating environment characterized by a narrowing policy space for central banks of advanced economies, the increasing scope of central bank objectives outside traditional monetary policy, greater global connectedness, and the rise of the Fourth Industrial Revolution. Moreover, it outlines the BSP’s policy directions and priorities going forward. More importantly, the article also discusses how, even in a complex operating environment, the benefits of BSP’s delivery of its mandates can be brought closer to the people.
Keywords: Banks and banking, Central; Bangko Sentral ng Pilipinas